The Relationship between Work Position and Complaints of Low Back Pain Among Nurses in the Inpatient Installation of the National Brain Center Hospital - Sondang Manurung; Mochamad Robby Fajar Cahya; Siswani Marianna; Nuniek Setyo Wardani; Khotimah Khotimah (Indonesian Journal of Global Health Research, 2025)
Low back pain (LBP) frequently occurs among nurses working in Inpatient Installations. 73.3% of LBP cases are exacerbated by non-ergonomic work positions. This study aims to determine the relationship between work position and complaints of LBP among nurses in the Inpatient Installation of the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono Jakarta. This research employs a quantitative research design with a cross-sectional approach, involving 77 nurses in the Inpatient Installation of the National Brain Center Hospital. Data collection was carried out using questionnaires, and data analysis was conducted using the Spearman Rank correlation coefficient. The results of this study indicate a relationship between work position and complaints of LBP in the Inpatient Installation of the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono Jakarta. The correlation test showed a significant relationship (p-value = 0.023 < 0.05) with a low correlation level (r = 0.258) and a positive correlation direction. It can be concluded that there is a relationship between work position and complaints of LBP among nurses in the Inpatient Installation of the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono Jakarta. The lower the risk of musculoskeletal disorders due to work position, the lower the level of disability due to LBP complaints. Nurses need to adopt ergonomic work positions to minimize the risk of LBP complaints. Hospitals should provide training on ergonomic work positions for nurses, supply ergonomic work equipment, and maintain the health of nurses to minimize LBP complaints.